Estimating the Prevalence and Identifying the Correlates of Sexting Behaviors Among Cambodian Male Adolescents - Seonhwa Kim; Youngran Yang (American Journal of Men's Health, 2023)
Male youths are more likely to experience peer pressure that encourages them to engage in risky behaviors than female youths, and this pressure can lead to an increased risk of sexting among male youths. This study aimed to investigate the prevalence of and factors associated with sexting among Cambodian male youths. The correlational cross-sectional study design was utilized. This study surveyed 647 Cambodian male youths aged 15 to 24 years. The measurement included sending or receiving messages (sexts) that contain sexually explicit messages, images, or videos, and affecting factors to sexting. Around 32.5% of participants sent sexts, and 38.9% received them. Open relationships, pornographic website use, perception of friends’ sexual activity, frequent thoughts about sex, higher sexual sensation-seeking tendencies, positive attitudes toward sex, and sexual experience were associated with increased likelihood of sending and receiving sexts. Based on the findings of this study, by offering suitable education, guidance, and intervention programs, we can effectively mitigate the adverse repercussions of sexting while fostering healthy sexual behaviors among youths.